Social solidarity economy and the community power among public policies co-building: A case in Vicente Guerrero Community in Tlaxcala, Mexico - Osorio Marín, Azucena Fabiola; Rojas Herrera, María Elena (Cooperativismo & Desarrollo, 2023)
The neoliberal capitalist system has caused a social and environmental crisis on a global scale, which has worsened due to the sars-CoV2 pandemic. The alternative path proposed by the Social Solidarity Economy (ESS by its Spanish acronym), argues that the valorization of capital and the maximization of profit as the main goals of production must be replaced by the expanded reproduction of life. Thus, organizations, collectives, groups, unions, cooperatives, etc., that belong to the ess seek to establish another economy that allows the perpetuation of life, for this reason, in its practice, they establish solidarity production structures based on co-property, democracy, equity and commitment to the environment. In Mexico, there is a wide diversity of organizations that belong to ess. The state of Tlaxcala has a long historic tradition of solidarity experiences and has community autonomy in its political representation through the Community Presidents’ election. Therefore, this article presents the results obtained through qualitative research conducted in the Vicente Guerrero Group, located in the town of the same name in the State of Tlaxcala, aiming to identify the way their organizational structure based on ess has started the co-building of local and state public policies, through joint actions that make use of community power oriented to the establishment of agroecological production.